Learning computer algorithms through dynamic visualizations: Benefits of 'AlgoRythmics' videos. - Katai, Zoltan; Osztian, Erika (Journal of Computer Assisted Learning, 2023)
Background: This study is the first to address the topic of schematic versus realistic dynamic visualization with particular focus on the human movement effect (HME) when the content to be learned takes the form of a computer algorithm. An AlgoRythmics dance choreography illustration (HM‐realistic) was compared with an abstract computer animation (schematic). Previous research in the field of dynamic visualizations found schematic illustrations to be more effective, but the examined realistic representations did not include HME. Objectives: The objective of this study was to explore the process of comprehension of computer algorithms from these two types of representations (abstract animation vs. dance choreography illustration). Methods: The experiment (pre‐test, study phase, post‐test) involved 84 undergraduate students and included the following conditions (2 × 2 between‐participants‐design): HM‐realistic → HM‐realistic, schematic → schematic, HM‐realistic → schematic, schematic → HM‐realistic. Results and Conclusions: The results reveal that: (i) the group of participants who saw the dance choreography twice outperformed those who saw the computer animation twice; (ii) dance choreography illustration is only beneficial if it is presented as the second visualization. These findings are apparently contrary to the conclusions of some relevant previous research in the field, but they are in line with recent results regarding the HME. Takeaways: Realistic dynamic visualizations can be more effective than schematic ones if they involve human movement. To benefit maximally from realistic visualization, students need to have previously viewed it or to have previously viewed the isomorphic schematic presentation of it. Lay Description: What is already known about this topic: Studies that researched whether animation aids learners' understanding of dynamic phenomena have reported mixed results.When human movement is used to illustrate the learning content, dynamic visualizations have consistently proven to be superior to static visualizations.Various studies have explored dynamic visualizations under different combinations of schematic and/or realistic representations. Participants who were exposed exclusively to realistic animations exhibited significantly lower performance compared to their counterparts in the other conditions. What this paper adds: Realistic dynamic visualizations can be more effective than schematic ones if they involve human movement.This result is apparently contrary to the conclusions of some relevant previous research in the field of schematic versus realistic dynamic visualizations, but it is in line with recent findings regarding the so‐called human movement effect.To benefit maximally from realistic visualization, students need to have previously viewed it or to have previously viewed the isomorphic schematic presentation of it. Implications for practice and/or policy: The study provides a new insight into the research field of dynamic visualizations and valuable guidelines for instructional design.